Length-Weight Relationships and Growth Patterns of Local Fishes of the Medium Perennial Vavuniya Reservoir, Sri Lanka - Patrick, A.E.S.; Kuganathan, S.; Edirisinghe, U. (University of Jaffna, 2021)
Linear regression analysis of length-weight relationships (LWRs) were studied to reveal the growth patterns of 380 specimens belonging to 10 species, 9 genera and 5 families of local fish in Vavuniya reservoir, Sri Lanka during January, 2013 to August, 2014. The regression coefficient value ‘b’ from LWR and statistical comparison from the ideal value (b=3) were used to find the growth patterns. Most of the local species showed isometric growth except Amblypharyngodon melettinus, Puntius sarana and Heteropneustes fossilis. Only Channa striata (b= 2.996, p=0.396) and females of Puntius dorsalis (b= 3.076, p=0.234) appeared in the catch throughout the study period and showed a strong correlation between length and weight. Combined sexes of, Glossogobius giuris (b= 3.178, p=0.216), Labeo dussumieri (b= 2.752, p=0.069) and females of Mystus keletius (b= 2.823, p=0.078) showed isometric growth. However, positive allometric growth for P. sarana females (b= 3.182, p=0.000) and negative allometric growth for combined sexes of H. fossilis (b= 2.613, p=0.001) were observed. During the drought period (July to August, 2014), A. melettinus, Esomus thermoicos (endemic) and Rasbora daniconius were observed at the sluice. E. thermoicos (b= 3.163, p=0.181) and R. daniconius (b= 3.065, p=0.393) obeyed the cubic law and showed an isometric growth pattern. However, A. melettinus showed a negative allometric growth (b= 2.367, p=0.002). Although, most of the local fish indicated isometric growth that reflected successful thriving, allometric growth reflected the sensitivity for environmental and habitat characteristics. Therefore, this study revealed the baseline evidence on the LWRs and the growth patterns, which could be considered for studying the survival of local fish to reach the optimal species richness and abundance.
Keywords: Length-weight relationship; Growth pattern; Local fish